TELAAH DEKONSTRUKSI KEKUASAAN DALAM NOVEL DARI FONTENAY KE MAGALLIANES KARYA NH. DINI DALAM PERSPEKTIF BUDAYA - -, Sugiarti (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2007)
This article concerns a study whose objective is to explain several issuesrelated to (1) a description of the domination, hegemony, and subordination ofcharacters in a novel, (2) the function of the power culture experienced by thecharacters, and (3) the meaning of power deconstruction in the novel.To reach the objective, the researcher conducting the study employs aqualitative-descriptive method. The source of data is the novel Dari Fontenay keMagallianes by Nh. Dini. The data are in the form of extracts taken from the noveland, complemented with the researcher's thoughts pertaining to issues related tosociety and power, collected through documentation and literary study withthorough understanding. Data validity is confirmed by employing a series of suchtechniques as (1) careful observation, (2) adequate literary reference, (3) peerdiscussion among parties sharing interest in literary works, and (4) triangulationby searching available articles for related information about the novelistconcerned.The results of the study show the following. (1) The types of powerdescribed in the novel are greatly reflected in the behavior of a character's husbandtoward his family (wife and children) and his colleagues. The power types could beexposed through the husband's attitude, ideology, and behavior in response to thesurrounding environment as part of his community. (2) The power culturefunctions to provide some characters with experiences suggesting that some socialissues have to be overcome by way of different unsatisfactory treatments. Inaddition, the power functions as a